Homometathesis and cross-metathesis coupling of phosphine-borane templates with electron-rich and electron-poor olefins - Dunne, K; Lee, SE; Gouverneur, V (2006)
Ruthenium-catalysed olefin cross-metathesis can be used to synthesise structurally diverse acyclic phosphines protected as their borane complexes. Homodimerisations have been investigated and proved successful only for the allyl-substituted borane-protected phosphines. In the presence of various olefinic partners, allyl-substituted P templates reacted in cross-couplings to give predominantly the E products but traces of the Z isomers were always detected in the crude reaction mixtures. In contrast, cross-metathesis of vinyl-substituted phosphine boranes took place with exclusive E-selectivity. Although the conversions were consistently very good to excellent, the yields of purified products were often significantly lower suggesting that some of the newly formed compounds are prone to decompose upon purification. © 2006 Elsevier B.V. All rights reserved.